Pertanggungjawaban Pribadi Direksi atas Perbuatan Melawan Hukum dalam Perseroan Terbatas - Agung, Bernardus Kidung; Wiwoho, Jamal (Indonesian Publication Center, 2026)
The Board of Directors, as an organ of the company, has the authority and responsibility to manage the company in accordance with the principles of good faith and prudence as stipulated in the Limited Liability Company Law. In practice, directors may act beyond their authority or engage in negligent or intentional conduct that causes losses to the company or third parties. This study aims to analyze the forms of directors’ liability for unlawful acts based on Article 1365 of the Civil Code and the Limited Liability Company Law. The research employs a normative legal method using statutory and conceptual approaches. The results indicate that directors may be held personally liable if they are proven to have committed fault or negligence in performing their duties resulting in losses, and if they fail to comply with the principles of fiduciary duty and duty of care. Therefore, personal liability of directors serves as an important legal instrument in promoting good corporate governance and providing legal protection for the company and third parties.